Social capital formation through farm woman groups in vegetable production in Kollam district - Revathy Chandran (Department of Agricultural extension, College of Agriculture, 2015)
The study entitled ‘Social capital formation through farm women groups in vegetable production in Kollam district’ was conducted in six panchayaths of Kollam district . The total number of respondents were 120 which included both farm women and extension facilitators. The main objectives of the study was to assess the scale of social capital formation, group efficiency, perception of farm women and extension facilitators regarding the group processes, constraints experienced by farm women in group process and comparing the efficiency of farming by individuals and by groups. In this study social capital can be operationally defined as those interactions which facilitates collective action. The dependent variables of the study were the extent of social capital formation, group efficiency and the planning, production and marketing aspects of the vegetables. The independent variables were the personal, socio-psychological characteristics of farm women. The data was collected using structured pre-tested interview schedule and social capital was measured using SOCAT (World Bank, 2010). Study revealed that majority of the respondents (82%) had medium level of social capital formation and the overall social capital in Kollam district is 61%.Karavaloor panchayath stood first in social capital formation with 71%.Social capital formation showed a significant positive relationship with annual income (0.216) and a significant negative relationship with area under vegetable cultivation (-0.218). Group efficiency index of the respondents were calculated and it was observed that majority of the respondents had medium group efficiency (53%). The study about planning, production and marketing aspects of vegetables revealed that in all these three aspects, most of the respondents showed a medium level of involvement, i.e. 57%,56% and58% respectively . Majority of the respondents i.e. 64% fall under medium category in gender role changes and recognition. 99% of farm women perceived that ‘groups are one of the best programmes implemented for them’ and ‘the agricultural operations could be done efficiently through groups’. 100% of the extension facilitators perceived that ‘groups provide a sustainable income and that it raised the confidence among farm women’. ‘Lack of working capital’ was identified as the major constraint of the study. Cent percent of the members prefer group farming and it can be concluded that social capital formation had improved over the years through women groups, but more efforts are needed to bring about a high level of social capital formation.